The Role of Aeration in Pond Management: FA6/FA021, 7/2002 - McGee, Michael; Cichra, Charles E. (EDIS, 2002)
The goal of most fish farmers is to maximize production and profits while holding labor and management efforts to the minimum. Risk of fish kills, disease outbreaks, poor water quality, and reduced feed conversion often result when efforts to increase production are unsupported by improved management strategies. This document is about aeration. This is a process that offers the most immediate and practical solution to water quality problems encountered at higher stocking and feeding rates. Aeration may be broadly classified into two different applications, emergency aeration and maintenance aeration. First published June, 1991.